Factors that Affect the Learning Behavior of Grade 10 Students at Rotonda National High School - Evangelio, Phoebe (International Journal of Research in Interdisciplinary Studies, 2025)
This survey was conducted to determine the factors that greatly affect the learning behavior of Grade 10 Students of Rotonda National High School. It utilized the SPSS Software to treat the information from the collected data. For the learning practices, the result showed that 56.5% of the students sometimes do self-learning management and 60 % of them answered that they sometimes use the learning facilities at school. There is not much difference between males and females in their self-learning management and utilization of learning facilities. The family income of the respondents sometimes affects their self-learning management and their utilization of learning facilities. For the support group between family and teachers, the majority of the students said that they often have their support at 52.9 -55 %. There is a statistically significant relationship between teacher support and the self-learning management of the students as calculated by Pearson’s r-value (0.246) which indicates a positive low correlation. In contrast, there is no significant relationship between teacher support and the utilization of learning facilities by the students. Family support, on the other hand, showed the result that there is a significant negative low correlation at a P-value of -.299. between family support and the self-learning management of the student, however, there is no significant relationship between family support and the utilization of self-learning facilities by the students.